2003
DOI: 10.1159/000073004
|View full text |Cite
|
Sign up to set email alerts
|

Between Acculturation and Ambivalence: Knowledge of Genetics and Attitudes towards Genetic Testing in a Consanguineous Bedouin Community

Abstract: The Bedouins of the Negev (Southern part of Israel) are a community at increased risk for genetic diseases and congenital anomalies as a result of frequent consanguinity (particularly patrilateral parallel-cousin marriage) and underutilization of prenatal genetic tests due to a Muslim ban on abortion. Objective: To assess the knowledge and attitudes of Bedouin schoolchildren and their teachers towards a community-based, premarital carrier-matching program aimed at reducing the prevalence at birth of genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…Compared to the Canadian public, which showed a relatively high mean knowledge score of 11 out of 16 [1], our study revealed a mean knowledge score of 5.3 out of 7. Our results were comparable to those for Israeli Bedouins [20]. The high knowledge level in our study may have been influenced by the nature of the study population who were young educated college students, and approximately two thirds of them were females.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Compared to the Canadian public, which showed a relatively high mean knowledge score of 11 out of 16 [1], our study revealed a mean knowledge score of 5.3 out of 7. Our results were comparable to those for Israeli Bedouins [20]. The high knowledge level in our study may have been influenced by the nature of the study population who were young educated college students, and approximately two thirds of them were females.…”
Section: Discussionsupporting
confidence: 85%
“…It is hoped that this reinforcement will provide students with a better basic knowledge of genetics and lead to a positive attitude toward genetic testing. Raz et al [20] concluded that a proper genetics education has improved the knowledge of genetics and attitudes toward genetic testing among Israeli Bedouins. Furthermore, the region is in critical need of more expertise on genetics and genetic testing because of the high prevalence of inherited and genetic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These programs are aimed to inform about the risks of consanguineous marriages and the association between consanguineous marriages and hereditary diseases and tests that could be done to prevent the birth of infants with congenital malformations. Raz et al (2003) assessed the knowledge and the attitude of schoolchildren and their teachers towards genetic testing in a consanguinity Bedouin community, 4 years after a community-based genetic educational program was established and found that knowledge on genetics and positive attitude towards genetic counseling were positively correlated. They also found that the participants were afraid from the stigma associated with positive carrier status, especially women because it can make it difficult for her to get married as first wife.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the participants were afraid from the stigma associated with positive carrier status, especially women because it can make it difficult for her to get married as first wife. In that case, it is better to require genetic screening before marriage and avoiding of marriages between carriers (Raz et al 2003). It is the duty of the public health professionals to ensure accessibility to counseling services and to periodically evaluate the knowledge and awareness of the health consequences of consanguineous marriages on offspring health.…”
Section: Discussionmentioning
confidence: 99%